Reducing Fertilizer and Avoiding Herbicides in Oil Palm Plantations—Ecological and Economic Valuations - Darras, Kevin F. A.; Corre, Marife D.; Formaglio, Greta; Tjoa, Aiyen; Potapov, Anton; Brambach, Fabian; Sibhatu, Kibrom T.; Grass, Ingo; Rubiano, Andres Angulo; Buchori, Damayanti; Drescher, Jochen; Fardiansah, Riko; et al. (Frontiers in Forests and Global Change, 2019)
Oil palm plantations are intensively managed agricultural systems that increasingly dominate certain tropical regions. Oil palm monocultures have been criticized because of their reduced biodiversity compared to the forests they historically replaced, and because of their negative impact on soils, water, and climate. We experimentally test whether less intensive management schemes may enhance biodiversity and lessen detrimental effects on the environment while maintaining high yields. We compare reduced versus conventional fertilization, as well as mechanical versus chemical weed control (with herbicides) in a long-term, full-factorial, multidisciplinary experiment. We conducted the experiment in an oil palm company estate in Sumatra, Indonesia, and report the results of the first two years. We measured soil nutrients and functions, surveyed above- and below-ground organisms, tracked oil palm condition and productivity, and calculated plantation gross margins. Plants, aboveground arthropods and belowground animals were positively affected by mechanical versus chemical weed control, but we could not detect effects on birds and bats. There were no detectable negative effects of reduced fertilization or mechanical weeding on oil palm yields, fine roots, or leaf area index; however, stem growth was enhanced under mechanical weeding. Also, we could not detect detrimental effects of the reduced fertilization and mechanical weeding on soil nutrients and functions (mineral nitrogen, bulk density, and litter decomposition), but water infiltration and base saturation tended to be higher under mechanical weeding, while soil moisture and microbial biomass varied with treatment. Economic performance, measured as gross margins, was higher under reduced fertilization. There might be a delayed response of oil palm to the different management schemes applied, so results of future years may confirm whether this is a sustainable management strategy. Nevertheless, the initial effects of the experiment are encouraging to consider less intensive management practices as economically and ecologically viable options for oil palm plantations.